STUDI UNJUK KERJA BOILER KAPASITAS 18 TON/JAM DI LINGKUNGAN PABRIK KELAPA SAWIT - Yuliani; Rinaldi; Sudarmo (Sainstek (e-Journal), 2017)
Boiler used in PT. Inti Indosawit Subur, Palm oil factory Buatan Satu in Pangkalan Kerinci namely Takuma WaterTube Boiler N 600 SA has long been used for it needs to be analyzed in detail in order to know the heat loss, boilerefficiency, actually after so long operated. The analysis is carried out with the purpose of knowing the boiler'sperformance to generate steam by referring to recorded operating data and determining the system that needs to becarried out for improvement or improvement of boiler performance. By using direct method, the analysis has been doneto boiler performance with steam capacity of 18 Ton / hr which is operated using fiber fuel and shell, Heating Value orheat value of combustion of fiber fuel and shell produced is 3,329,301 Kkal / kg, It can be concluded that the heating value of fiberglass and shell fuel 3,329,301 Kkal / kg, The amount of fuel used based on field data for steam capacity of18,000 kg / hour, it will need fiber and shell fuel of 4700 kg / hour every hour. While the amount of fuel usedtheoretically for steam capacity of 18,000 kg / hour, it will need fiber and shell fuel 4,126,542 kg / hour. Here we cansee there is a deviation that occurs very significant between field data and theoretical that is 573,458 kg / hour. Airrequired for combustion 27,680.84 kg / hour every hour, heat produced by burning fuel 13,051,575 Kcal / hour andboiler efficiency is the ratio between heat consumption (hot useful) with heat supply, from calculation analysis obtainedamount of usefulness Boiler is 86.501%. Therefore it can be said that the boiler is still feasible to operate